On the Verification Theorem of Dynamic Portfolio-Consumption Problems with Stochastic Market Price of Risk - Honda, Toshiki; Kamimura, Shoji (Asia-Pacific financial markets, 2011)
In this paper, we study a dynamic portfolio-consumption optimization problem when the market price of risk is driven by linear Gaussian processes. We show sufficient conditions to verify that an explicit solution derived from the Hamilton-Jacobi-Bellman equation is in fact an optimal solution to the portfolio selection problem.